Hepatocellular carcinoma and miRNAs: An in silico approach revealing potential therapeutic targets for polyphenols - Chuffa, Luiz Gustavo de Almeida [UNESP]; Souza, Milena Cremer de; Cruz, Ellen Mayara Souza; Ferreira, Francielle Belinelli; de Morais, Juliana Maria Bitencourt; Seiva, Fábio Rodrigues Ferreira (Elsevier, 2022)
Background: Identifying innovative and effective therapeutic agents is imperative for treating hepatocellular carcinoma (HCC). Natural phytochemical compounds may be a feasible glimmer of hope as more than 8,000 phenolic structures are currently known, and several of them are efficient in treating different types of cancer. Purpose: MicroRNAs can modulate tumor cell response to growth signals, apoptosis and replication rates, new blood vessel formation, tissue invasion, and dissemination. We disclosed herein how phenolic compounds, influencing miRNAs-regulated genes, may exert their antitumor activities. Methods: After a systematic review of the literature, we applied distinct in silico tools and approaches to query miRNA expression after treatment with polyphenols, determined some of the miRNA effects over target genes, elaborated protein networks and enriched their pathways, as well as presented differentially expressed genes (DEGs) found in HCC patients. Our predictions were corroborated by several in vitro and in vivo experimental studies that we presented and discussed. Results: Phytochemicals such as berberine, curcumin, EGCG, luteolin, and quercetin are promising candidates capable of regulating different miRNAs while exerting their antitumoral effects through distinct molecular mechanisms. MiRNAs such as miRNA-122 and -34a deserve deep investigations, as they were found to be over and down-expressed by more than one polyphenol. MiRNA-regulated genes took part in molecular mechanisms such as cell death, through p53, bcl-2, and SMAD modulation; energy metabolism, by regulating PI3K/Akt pathway; antiproliferative events, mediated by Ras, c-Kit, and β-catenin; and epigenetics events, involving SIRT, HDAC, and DNMT family members. Tumor microenvironment modulation, by NOTCH1 and VEGFA, is also a potential mechanism related to polyphenols’ effects. We reported that polyphenols have specific drug ability and anticancer biological activities. Among the DEGs, 4 of them (e.g., EZH2, HRAS, STMN1, VEGFA), are candidate genes for miRNA modulation. The expression profile of gene subsets that are frequently altered in HCC patients was also characterized. Conclusion: The capacity of polyphenols to regulate miRNA actions may have a significant impact on the treatment of liver tumors; experimental and clinical studies dedicated to confirming our findings are further needed.
Keywords: Bioinformatics; Liver cancer; Long noncoding RNA; Polyphenolic